ROLE OF AUDIT COMMITTEE IN THE FRAUD PENTAGON AND FINANCIAL STATEMENT FRAUD - Hexana Sri Lastanti (International Journal of Contemporary Accounting, 2020)
The research aims to detect financial statement fraud by means of Fraud Pentagon, with Audit Committee as a moderating variable. Variables applied in this research are a dependent variable in form of Financial Statement Fraud, an independent variable in form of Fraud Pentagon consisting of Pressure, Opportunity, Rationalization, Competence or Capability and, Arrogance factors, and Audit Committee as a moderating variable. Meanwhile, this research analyzes 49 manufacturing companies listed on Indonesia Stock Exchange (IDX) during 2016-2018 as the research sample and conducts 149 observations by means of a purposive sampling method. The research finds out that Pressure, Opportunity, and Rationalization determine Financial Statement Fraud with respect to the existence or inexistence of moderation by the size of Audit Committee. Other factors (i.e., Capability and Arrogance) most likely are insignificant to Financial Statement Fraud. This research suggests that the corporate management should cautiously take into account the Pressure factor measured by financial stability, the Opportunity factor measured by effective monitoring, and the Rationalization factor measured by change in auditor. Those three aspects are highly significant to Financial Statement Fraud. Besides, the corporate management should also enhance the effectiveness of Audit Committee because this variable is able to magnify the effect of Pressure, Opportunity, and Rationalization factors on Financial Statement Fraud.